PEMBUATAN SEDIAAN LULUR SERBUK TRADISIONAL BIJI PEPAYA (Carica papaya L) DAN PATI KEDELAI (Glycine max L) UNTUK MENGATASI KULIT KERING - Nurmala, Tiya; Handayani, Reti Puji; Farhan, Farhan (Sekolah Tinggi Ilmu Kesehatan Holistik, 2019)
Background: Everyone has suffered from skin dryness, itching, scaling and redness due to various causes. Xerosis cutis dry skin or a skin disorder where the skin becomes rough, scaly, wrinkled and less elastic than normal and dry skin on palpation. The prevalence of xerosis in Indonesia is 50% -80%, while in some other countries such as Brazil, Australia, Turkey, and others are 35% -70%. Caring for the skin on a regular basis can be done using traditional scrubs from natural materials. The use of papaya seeds usually just thrown or planted or used as seed for cultivation, when in fact the papaya seeds can be processed into a useful preparation. Papaya seeds rich in benefits for the skin. In addition to dry skin treatment can also be done using soy beans and olive oil. Objective: Create and test the stability of the preparation is organoleptic and pH in the preparation of traditional herbal powders for dry skin from the seeds of papaya (Carica papaya L) and starch soybean (Glycine max L) with olive oil as an aroma enhancer. Methods: This study was action research or action research with the observation sheet instruments. Testing the stability of traditional powder herbal preparation made for 3 weeks at cool temperature of 100C and 250C room temperature. Result: Indicates that the preparation of traditional herbal papaya seed powder and soy starch stored at a cool temperature of 100C has the organoleptic stability of shape, smell, color and absence of fungi and have a pH that is better than the room temperature storage at 250C. Conclusion: This study provides results and good stability for 3 weeks. It is expected that further research can do the testing other than organoleptic test and pH with different dosage forms of the ingredients of papaya seeds and soybeans.